Development of tissue engineered strategies combining stem cells and scaffolds aimed to regenerate bone and osteochondral interfaces - Rodrigues, Márcia T. (2011)
Tese de doutoramento em Engenharia de Tecidos, Medicina Regenerativa e Células Estaminais